Assessment of oxidative stress in breast cancer patients: a hospital based study - Bhattacharjee, Jagruti; Jogdand, Sangita; Shinde, R. K.; Goswami, Sourav (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Oxidative stress occurs as a result of the disturbance in the balance between the production of reactive oxygen species (free radicals) and antioxidant defenses. This is regarded as a possible etilogical factor in production of breast carcinoma, which is the most cmmon cancer among the females both globally as well as in India. Oxidative stress also plays an important role in progression of cancer breast. This study was conducted to compare the levels of superoxide dismutase (SOD) and malondialdehyde (MDA) in breast cancer patients and normal age matched female participants. Methods: This study was conducted in AVBR Hospital, Sawangi (Meghe) among 30 female breast cancer patients admitted in the surgery ward for treatment after being diagnosed with the disease, who attended the hospital from July 2016 to June 2017. Breast cancer patients of stage I and II were included in the study. Patients suffering from any other diseases apart from breast cancer like diabetes, hypertension, thyroid illnesses and other sort of cancers are excluded from the study. For each of the study participant, age and sex matched controls were selected who were mostly the relatives of patients attending the hospital and were devoid of any illnesses. Venous blood sample was collected from all the patients as well as the controls that were used for determination of the levels of SOD (superoxide dismutase) and MDA (malondialdehyde). Written informed consent was taken from all the study participants before drawing the blood samples. Results: Authors have measured the markers of oxidative stress in breast cancer patients after diagnosis of breast cancer and compared theses blood levels with those of the controls. The mean MDA (nmol/ml) levels for the breast cancer patients and the controls were 26.14 and 15.83 respectively, while the SOD (U/gm Hb) levels were 0.12 and 0.16 respectively and the difference of the mean were statistically significant (p value <0.01). Conclusions: There is presence of increased oxidative stress in breast cancer patients as compared to the healthy controls.